Sentinel Lymph-Node Biopsy in Early-Stage Cervical Cancer: The 4-Year Follow-Up Results of the Senticol 2 Trial - Favre, Guillaume; Guani, Benedetta; Balaya, Vincent; Magaud, Laurent; Lecuru, Fabrice; Mathevet, Patrice (Frontiers in Oncology, 2021)
Introduction: Senticol 2 is a randomized multicenter trial in the treatment of early-stage cervical cancer patients. The aim of the Senticol 2 study was to compare the effect of sentinel-lymph-node biopsy (SLNB) to that of SLNB + pelvic lymphadenectomy (PLND), and to determine the postoperative lymphatic morbidity n the two groups. Here, we report a secondary objective of this study: the follow-up. Material and Methods: In the Senticol 2 trial, patients underwent a laparoscopy with a sentinel-node-detection procedure and were randomized into two groups, namely: Group A, in which participants received SLNB, and Group B, in which participants received SLNB + PLND. Patients with an intra-operative macroscopically suspicious lymph node, were given a frozen-section evaluation and were randomized only if the results were negative. All of the patients received follow up with a clinical examination at 1, 3, and 6 months after surgery, and then every 3–4 months after that. Results: Disease-free survival after 4 years for the SLNB group and the SLNB + PLND group were 89.51% and 93.1% (p = 0.53), respectively. The only statistical factor associated with recurrence in the univariate analysis was the adjuvant radiotherapy. No other factors, including the age of the patients, histological type, tumor size, lymph-vascular space invasion (LVSI), and positive nodal status, were significant in the univariate or multivariate analyses. The overall survival rates after 4 years in the SLNB and SLNB + PLND groups were 95.2% and 96% (p = 0.97), with five and four deaths, respectively. The univariate and multivariate analyses did not find any prognostic factors. Conclusions: This randomized study confirmed the results of the Senticol 1 study and supports the sentinel lymph-node (SLN) technique as a safe technique for use in patients with early-stage cervical cancer treated with SLNB only. Disease-free survival after 4 years was similar in patients treated with SLN biopsy and patients who underwent a lymphadenectomy.